EFEKTIFITAS UNITED NATIONS PROGRAMME ON HIV AND AIDS (UNAIDS) MENANGANI HIV/AIDS DI INDONESIA TAHUN 2009-2012 - Idayu, Prima Rita; Pahlawan, Indra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This research is is to exsplain about the internasional coopration betweencountry and international organizations. The focus of this study is to eksplainUNAIDS as internasional organization that hold global HIV/AIDS. HIV /AIDS is a health issue that is deserves to be taken internationally. To handlethis problems, Indonesia does cooperation with international organizations,United Nations Programme on HIV and AIDS ( UNAIDS ) . unaid is createdby the global responses toward the increasing and expansion of HIV/AIDSwhich is increase highly. Indonesia is one of the countries that facesincreasing in HIV from year to year . The highest prevalence of HIV inIndonesia is through drug injection and sexual risk. The cooperationUNAIDS and Indonesian began in 1996 , with the mission of preventing HIVis providing care support for those infected with HIV / AIDS and reduceindividual and communities to HIV / AIDS then reduce the social andeconomical effects.The implementation of the UNAIDS programme inindonesia is not effective. Harm reduction is program recommended byUNAIDS in Indonesia. The implementation of this program has a lot ofobstacles. Failure to change behavior of drug addicts to use clean needlesmake the spread of HIV is increasing. Another obstacles is the HarmReduction program against Indonesian law other than beside that thisprogram is not accepted by the majority of Muslims in Indonesia. thecondition of indonesian geography widely that separates thousand islandsalso make dissemination of information to be complicated.Key Words: HIV/AIDS, UNAIDS, drug injection,sexual , Harm Reduction